Internetowe źródła informacji na potrzeby badań marketingowych gmin - Krakowiak, Monika; Jakubowska, Agata (Internet Sources of Information for Commune's Marketing Research, 2006)
Internet thanks to easy access, simple maintenance and low costs of net sharing, provides everyone with equal access to information, both secondary and primary one. Polish local authorities still use its research potential to a larger degree for indirect studies only. One of significant determinants of development of Internet primary research is the attitude of local authorities towards this form of direct analysis.This paper presents a field research results which concerned the usage of the Internet in the marketing research conducted by the local governments
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 640-645